Putting fire on the map of Brazilian savanna ecoregions. (15th October 2021) - Silva, Patrícia S.; Nogueira, Joana; Rodrigues, Julia A.; Santos, Filippe L.M.; Pereira, José M.C.; DaCamara, Carlos C.; Daldegan, Gabriel A.; Pereira, Allan A.; Peres, Leonardo F.; Schmidt, Isabel B.; Libonati, Renata
Abstract: The Brazilian savanna (Cerrado) is considered the most floristically diverse savanna in the world, home to more than seven thousand species. The region is a mosaic of savannas, grasslands and forests whose unique biophysical and landscape attributes are on the basis of a recent ecoregional map, paving the way to improved region-based strategies for land management actions. However, as a fire-prone ecosystem, Cerrado owes much of its distribution and ecological properties to the fire regime and contributes to an important parcel of South America burned area. Accordingly, any attempt to use ecoregion geography as a guide for management strategies should take fire into account, as an essential variable. The main aim of this study is to complement the ecoregional map of the Cerrado with information related to the fire component. Using remotely sensed information, we identify patterns and trends of fire frequency, intensity, seasonality, extent and scar size, and combine this information for each ecoregion, relying on a simple classification that summarizes the main fire characteristics over the last two decades. Results show a marked north-south fire activity gradient, with increased contributions from MATOPIBA, the latest agricultural frontier. Five ecoregions alone account for two thirds of yearly burned area. More intense fires are found in the Arc of Deforestation and eastern ecoregions, while ecoregions in MATOPIBA display decreasing fire intensity. An innovative analysis of fire scars stratified by size class shows that infrequent large fires are responsible for the majority of burned area. These large fires display positive trends over many ecoregions, whereas smaller fires, albeit more frequent, have been decreasing in number. The final fire classification scheme shows well defined spatially-aggregated groups, where trends are found to be the key factor to evaluate fire within their regional contexts. Results presented here provide new insights to improve fire management strategies under a changing climate. Graphical abstract: Image 1 Highlights: There are very distinct regional fire behaviours in Cerrado. Fire has a well-defined north-south gradient related to economic development. Few large fires during the dry season are responsible for most of the burned area. MATOPIBA, the latest agricultural frontier, shows increasing fire activity. Adding fire characteristics on ecoregions allows improved local management policies.